Global supply chains, standards and the poor [ how the globalization of food systems and standards affects rural development and poverty - Swinnen, Johan F. M. , 1962- (CABI, 2007)
Using original research from Asia, Africa, Europe and Latin America, this book reviews the recent restructuring of the global agri-food industry and the dramatic rise of global retail chains in developing and transition countries. It focuses on the privte standards and requirements imposed by multinational companies investing in these countries and the resulting changes to existing supply chains. It also examines the impact of these changes on local producers, particularly poor farmers, and considers the long-term policy implications in terms of growth and poverty.